Acute coronary syndrome associated cardiogenic shock in the catheterization laboratory: peripheral veno-arterial extracorporeal membrane oxygenator management and recommendations - Ehrenberger, Réka; Németh, Balázs T.; Kulyassa, Péter; Fülöp, Gábor A.; Becker, Dávid; Kiss, Boldizsár; Zima, Endre; Merkely, Béla; Édes, István F. (Frontiers in Medicine, 2023)
Cardiogenic shock (CS) in acute coronary syndrome (ACS) is a critical disease with high mortality rates requiring complex treatment to maximize patient survival chances. Emergent coronary revascularization along with circulatory support are keys to saving lives. Mechanical circulatory support may be instigated in severe, yet still reversible instances. Of these, the peripheral veno-arterial extracorporeal membrane oxygenator (pVA-ECMO) is the most widely used system for both circulatory and respiratory support. The aim of our work is to provide a review of our current understanding of the pVA-ECMO when used in the catheterization laboratory in a CS ACS setting. We detail the workings of a Shock Team: pVA-ECMO specifics, circumstances, and timing of implantations and discuss possible complications. We place emphasis on how to select the appropriate patients for potential pVA-ECMO support and what characteristics and parameters need to be assessed. A detailed, stepwise implantation algorithm indicating crucial steps is also featured for practitioners in the catheter laboratory. To provide an overall aspect of pVA-ECMO use in CS ACS we further gave pointers including relevant human resource, infrastructure, and consumables management to build an effective Shock Team to treat CS ACS via the pVA-ECMO method.